What is an adequate margin for infiltrative soft-tissue sarcomas?. Issue 2 (February 2020) - Fujiwara, Tomohiro; Stevenson, Jonathan; Parry, Michael; Tsuda, Yusuke; Tsoi, Kim; Jeys, Lee
Abstract: Objectives: What constitutes an adequate margin of resection for infiltrative subtypes of soft-tissue sarcomas remains unclear. We aimed to determine the prognostic significance of the margin in millimetres for myxofibrosarcoma (MFS) and undifferentiated pleomorphic sarcoma (UPS). Methods: 305 patients diagnosed with either a high-grade, localised MFS (n = 98) or UPS (n = 207) were included. The relationship of closest margin in millimetres to viable tumour and oncological outcomes was analysed. Results: The overall local recurrence (LR) rate for all patients were 12%: 19% with positive margin and 10% with negative margin ( p  = 0.051). The LR rate was similar in patients with negative but <10 mm margin; 13%, 6%, 15%, 17% with 0.1–0.9 mm, 1.0–1.9 mm, 2.0–4.9 mm, and 5.0–9.9 mm margin, respectively. However, the LR rate decreased to 3% if the margin was ≥10 mm. By the R- or R+1-classification, the 10-year cumulative probability of LR was 9%, 15%, 48% for R0, R1, R2 resections, respectively, which was not sensitive enough to stratify the LR risk in patients with negative margins. However, the cumulative probability of LR was significantly stratified by metric distance; the 10-year cumulative LR probability was 3%, 14%, 25% with ≥10.0 mm, 0.1–9.9 mm, and 0 mm, respectively ( p  = 0.026). A trend towards improved local control by adjuvant radiotherapy was seen in patients with 0–9.9 mm margin ( p  = 0.078). Conclusion: The resection margin, when measured as a metric distance, correlates with a reduction in LR, and appears to be more significant on local control than radiotherapy. To minimise the risk of LR, a margin distance of at least 10 mm is advocated for MFS and UPS.